Pengaruh pengelolaan keuangan terhadap keberhasilan UMKM: Kajian berdasarkan hasil penelitian terkini - Oktav, Real Lea; Suci, Waladia; Rahmi, Abdul (Journals of Indonesian Multidisciplinary Research, 2024)
Good financial management is a key factor in determining the success of Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze and evaluate previous research on the relationship between financial management and MSME success. A Systematic Literature Review (SLR) was conducted on 40 selected articles, consisting of 30 national and 10 international journal articles published between 2019 and 2024. The findings show that research on this topic peaked in 2022, with qualitative approaches being the most frequently used methods. The most common variables studied include financial management, financial literacy, as well as financial recording and planning, while MSME performance was the primary dependent variable. Quantitative studies typically used sample sizes ranging from 30 to 120 respondents, while qualitative studies involved 5 to 30 informants. Data analysis tools were dominated by descriptive approaches and simple regression techniques, with limited use of advanced methods such as SEM and PLS. Overall, the findings indicate that financial management plays a vital role in improving MSME success, although its effectiveness is also influenced by financial literacy and external environmental factors. This review provides a foundational reference for future strategies to strengthen and support MSMEs.